Developmental abnormalities and age-related neurodegeneration in a mouse model of Down syndrome - Holtzman, David M. (The National Academy of Sciences of the USA, 1996)
To study the pathogenesis of central nervous system abnormalities in Down syndrome (DS), we have analyzed a new genetic model of DS, the partial trisomy 16 (Ts65Dn) mouse. Ts65Dn mice have an extra copy of the distal aspect of mouse chromosome 16, a segment homologous to human chromosome 21 that contains much of the genetic material responsible for the DS phenotype. Ts65Dn mice show developmental delay during the postnatal period as well as abnormal behaviors in both young and adult animals that may be analogous to mental retardation. Though the Ts65Dn brain is normal on gross examination, there is age-related degeneration of septohippocampal cholinergic neurons and astrocytic hypertrophy, markers of the Alzheimer disease pathology that is present in elderly DS individuals. These findings suggest that Ts65Dn mice may be used to study certain developmental and degenerative abnormalities in the DS brain.